Linux 2.4 implementation of Westwood+ TCP with rate-halving: a performance evaluation over the Internet - A. Dell’Aera; L.A. Grieco; S. Mascolo (2004 IEEE International Conference on Communications (IEEE Cat. No.04CH37577), 2004)
The additive increase/multiplicative decrease probing paradigm is at the core of TCP congestion control. To improve the classic Reno/New Reno congestion control algorithms, the recent Westwood+ TCP proposes to substitute the multiplicative decrease phase with an adaptive decrease phase, which takes into account an end-to-end estimate of the available bandwidth obtained by filtering the stream of returning ACKs. This paper aims at evaluating the performance of Westwood+ TCP over the real Internet. For that purpose, a Linux 2.4.19 implementation of Westwood+ TCP has been developed and compared with an implementation of New Reno. More than 4000 files, with different sizes, have been uploaded via ftp from a host at the Politecnico of Bari (South of Italy) to three remote servers, which are located at Parma (North of Italy), Uppsala University (Sweden) and University of California Los Angeles (UCLA, California). Experimental results indicate that Westwood+ TCP improves the goodput with respect to New Reno TCP over paths with a bandwidth delay product larger than few segments. In particular, goodput improvements up to 40-50% have been measured when transmitting data from Politecnico of Bari to Uppsala or UCLA servers. Currently, Westwood+ TCP support is available in the official Linux kernel. It was included both in the kernel 2.4.x from version 2.4.26-prel on and in the kernel 2.6.x from version 2.6.3-rcl on.
Keywords: Linux; Internet; Kernel; Bandwidth; Filtering algorithms; Programmable control; Adaptive control; Phase estimation; Adaptive filters; Information filtering